Waves of Pixels and Word-generated Algorithms: Drone Poetry as a Collaborative Practice between Machine and Human in Waveform by Richard A. Carter - Ostalska, Katarzyna (Text Matters: A Journal of Literature, Theory and Culture, 2023)
The following article explores the creative collaborative practices in digital poetry between more-than-human agents. Richard A. Carter’s artistic project Waveform (2017–) makes one reconsider the ways in which multimodal and web-based encounters of image, word, sound and movement, and, in the case of Carter’s airborne drone, also the political and military, redefine “a literary text” via nonhuman extended perception. Drone-generated poetry challenges a human-centered (literary) perspective, raising questions about AI’s creativity and code’s generative and aesthetic, and not only functional, potential. The article, drawing upon Raichlen, introduces a comparative platform of waves’ mechanics to render the complexity of multimedial digital poetic writing. The focal analytical material provided by Carter results from the (human, machine) vision (of the moving waves) translated into words, generated by the drone, and edited by the human. The article studies the creative process in which the collaboration between more-than-human entities, as its outcome, produces poetic work of artistic value and literary merit.